∑(M[sub 2])[sub i]–AN EVALUATION. - Vatter, W. J. (The Accounting Review, 1963)
Accounting assumes continuity, but this means that the financial statements prepared by breaking the continuous stream of activity into periodic segments, even under the most favorable circumstances, provisional in character. Continuity serves to complement and strengthen the concept of earning power, the income statement is a means of making available a section of the continuous flow of cost and revenue to exhibit management's effectiveness in handling available resources. In consequence, it should recognize all special and non-recurring losses and gains, as these elements modify the long run income stream. The basic idea of measured consideration" is broad enough to encompass the entire range of accounting measurements, it is superior to "value" because values bring in measurements of another and different order. Value would include amounts for utilities not measurable except by one's own judgment until a sale confirms this added utility its measurement is not objectively possible. However, the use of money and price as measurement devices should not obscure the fact that the significant element behind the accounts is service potentialities, which, when exchanged, bring other service-potentialities into the enterprise.